Perilaku Siswa yang Tidak Dikehendaki (Off Task Behavior) dan Penanganan Konselor - Ridni Eliza; Neviyarni Neviyarni (Prodi Bimbingan dan Konseling Islam, 2020)
The purpose of this research was to describe the forms, causes, counselor handling, and counselor in dealing with barriers off-task behavior of a student in Ash - Shidiiqi Islamic Primary School Jambi. The methods used to collect the data are interviews, observation, and documentation. The subject in this research is the headmaster, 2 (two) counselors, 7 (seven) teachers, 3 (three) subject teachers, and 7 (seven) students who have off-task behavior. The results showed that the off-task behavior of students going on Ash - Shidiiqi Islamic Primary School Jambi, around the class, talking with friends, play stationery such as pen, pencil, eraser, or ruler, play or throw paper, do not pay attention to the teacher’s explanation, but the head on the table, make a noise, climbed to the top of the seat, out of the class, joking with friends, drawing on paper, scribble table, opened other textbooks, do homework,. The causes of student conduct off-task behavior consist of internal factors and external factors. Internal factors include the adaptation of school and difficulty in learning. While external factors that underlie the emergence of off-task behavior of the student is the influence of friends and lack of attention from the teacher. There are various kinds of treatment used by a counselor, which are reprimand or warned by giving advice, in addition to dealing with off-task behavior counselor collaborate with classroom teachers and subject teachers to apply operant conditioning by using reinforcement and punishment techniques. Barriers faced counselor is limited provision of counseling.